Kinetics and Thermodynamics Studies of Copper(II) Adsorption onto Activated Carbon Prepared from Salacca zalacca Peel - Dewi Yuanita Lestari; Endang Widjajanti Laksono (Molekul, 2020)
Highly porous and stable materials, such as alumina, silica, carbon, zeolite, and bentonite,  are well known and have been used as metal ion adsorbents. However, the use of biogenic carbon as adsorbent is relatively rare. The adsorption of copper(II) onto activated carbon extracted from Salcaca zalacca peel was studied. The effect of initial copper concentration, contact time, and a series temperature was studied. Adsorption was carried out in a batch technique. The adsorption equilibrium was reached after 60 minutes of contact time. The adsorption data had a better fitting line for the Langmuir isotherm model. The Langergren and also Ho and Mc Kay equations were used to predict the adsorption kinetics. The adsorption process obeyed a second-order kinetics model. The Thermodynamic parameters were ∆H°= -42.4180 kJ/mol; ∆S°= -0.0843 kJ/mol; ∆G°<0. These values indicated that the adsorption was exothermic and spontaneous. The low ∆G° value revealed that the main mechanism controlling the adsorption process was physisorption.